Pelatihan Batik Tulis Motif Kontemporer untuk Meningkatkan Kreativitas dan Kemandirian Karang Taruna di Sidomukti Gresik - Ubaidillah; Abdul Hakam; Ajrina Valentine Marhadyta; Risma Ayu Kinanti; Qurrota A’yun Zakiyyati (Khidmatuna: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to equip the youth of the Karang Taruna in Sidomukti Village, Kebomas District, Gresik Regency, with contemporary hand-drawn batik skills to enhance creativity and economic independence. The main problem faced by the partners is the lack of productive activities and limited specialized skills with high economic value for local youth. The method used in this service is participatory training, which includes socialization, technical batik training (ranging from contemporary motif design, the waxing process, to coloring), and entrepreneurship management mentoring. The results of the service show an increase in the participants' technical skills in producing innovative batik works that are not restricted to traditional patterns. Furthermore, this activity has successfully fostered youth independence through the formation of a local-based creative business unit. This service contributes to the development of non-formal educational science, specifically in community empowerment methods based on arts and culture to create economic empowerment in the digital era.